Decay Dynamics of 3‐methyl‐3‐pentene‐2‐one from the light absorbing S2(ππ*) state ‐ Resonance Raman Spectroscopy and CASSCF Study. (27th April 2014) - Xu, Zhu‐Bing; Pan, Sheng; Yang, Yi; Xue, Jia‐Dan; Zheng, Xuming; Xie, Bin‐Bin; Fang, Wei‐Hai
<x xml:space="preserve">Abstract</x> The photophysics of 3‐methyl‐3‐pentene‐2‐one (3M3P2O) after excitation to the S2(ππ*) electronic state were studied using the resonance Raman spectroscopy and complete active space self‐consistent field (CASSCF) method calculations. The A‐band resonance Raman spectra were obtained in cyclohexane, acetonitrile, and methanol with excitation wavelengths in resonance with the first intense absorption band to probe the structural dynamics of 3M3P2O. The B3LYP‐TD/6‐31++G(d, p) computation was carried out to determine the relative A‐band resonance Raman intensities of the fundamental modes, and the result was used to reproduce the corresponding fundamental band intensities of the 223.1 nm resonance Raman spectrum and thus to examine whether the vibronic‐coupling existed in Franck‐Condon region or not. CASSCF calculations were carried out to determine the minimal singlet excitation energies of S1, FC, S1, min (nπ*), S2, FC, S2, min (ππ*), the transition energies of the conical intersection points Sn/Sπ, Sn/S0, and the optimized excited state geometries as well as the geometry structures of the conical intersection points. The A‐band short‐time structural dynamics and the corresponding decay dynamics of 3M3P2O were obtained by the analysis of the resonance Raman intensity pattern and CASSCF computations. It was revealed that the initial structural dynamics of 3M3P2O was towards the simultaneous C3=C4 and C2=O7 bond elongation, with the C3=C4 bond length lengthening greater at the very beginning, whereas the C2=O7 bond length changing greater at the later evolution time before reaching the CI(S2/S1) conical intersection point. The decay dynamics from S2(ππ*) to S1(nπ*) via S2(ππ*)/S1(nπ*) in singlet realm and from S1(nπ*) to T1(nπ*) via ISC[S1(nπ*)/T2(ππ*)/T1(nπ*)] in triplet realm are proposed. Copyright © 2014 John Wiley & Sons, Ltd.